2017
DOI: 10.1016/j.rser.2016.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Liquefied natural gas: Could it be a reliable option for road freight transport in the EU?

Abstract: Approximately one-quarter of the total greenhouse gases (GHG) emissions in Europe can be attributed to the transport sector, with petroleum-derived fuels dominating road transport. In the current environmental and economic context, the use of less polluting alternative fuels simultaneously providing security of supply and optimal energy storage is encouraged. Natural gas (NG) technology for transportation is mature and extended through the use of the compressed form in urban and light vehicles. The introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 42 publications
(85 reference statements)
0
52
0
Order By: Relevance
“…As illustrated in Figure 4, the innovations related to higher environmental sustainability scored higher grades from the respondents. Exceptions were LNG as fuel and catalyst converters, which are more relevant to maritime transports (although in fact LNG is being experimented with in road transports [50][51][52]). While shipment monitoring was revealed as a topic of high interest for transportation companies during the interviews, technologies such as blockchain and IoT received a low score on interest during the survey.…”
Section: Survey Resultsmentioning
confidence: 99%
“…As illustrated in Figure 4, the innovations related to higher environmental sustainability scored higher grades from the respondents. Exceptions were LNG as fuel and catalyst converters, which are more relevant to maritime transports (although in fact LNG is being experimented with in road transports [50][51][52]). While shipment monitoring was revealed as a topic of high interest for transportation companies during the interviews, technologies such as blockchain and IoT received a low score on interest during the survey.…”
Section: Survey Resultsmentioning
confidence: 99%
“…The transport sector in the EU countries in 2009 was responsible for 20% of all emissions. One of the most obvious advantages of LNG as a fuel is visible if environmental considerations are taken into account [8,12,[27][28][29][30][31][32][33]. The European Union encourages the development of alternative fuels to reduce carbon footprint [34].…”
Section: Ecological Aspectsmentioning
confidence: 99%
“…As a result, the transportation sector is almost completely fueled by conventional liquid fuel, covering approximately 90% [81]. Osorio-Tejada et al [82] reported that one-quarter of the GHG emissions in Europe emanate from the transport sector. Recently, European countries widely encourage the use of natural gas as a vehicle fuel to combat the overgrowing greenhouse-gas emissions.…”
Section: Natural Gas In the Transportation Sectormentioning
confidence: 99%